2005
DOI: 10.1104/pp.105.062950
|View full text |Cite
|
Sign up to set email alerts
|

Lateral Diffusion of CO2 in Leaves Is Not Sufficient to Support Photosynthesis

Abstract: Lateral diffusion of CO 2 was investigated in photosynthesizing leaves with different anatomy by gas exchange and chlorophyll a fluorescence imaging using grease to block stomata. When one-half of the leaf surface of the heterobaric species Helianthus annuus was covered by 4-mm-diameter patches of grease, the response of net CO 2 assimilation rate (A) to intercellular CO 2 concentration (C i ) indicated that higher ambient CO 2 concentrations (C a ) caused only limited lateral diffusion into the greased areas.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
64
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
3

Relationship

3
7

Authors

Journals

citations
Cited by 74 publications
(69 citation statements)
references
References 35 publications
3
64
0
Order By: Relevance
“…Measurements of maximum and actual photosynthetic efficiency were identical to the wild type in areas with stomata; however, leaf areas without stomata showed lower maximum and actual photosynthetic efficiency, illustrating that stomatal patterning determined CO 2 concentration and photosynthesis across the leaf lamina and that lateral fluxes of gas could not compensate for reduced vertical diffusion as a result of reduced stomatal numbers (Büssis et al, 2006). This work agrees with reports that suggest that lateral fluxes can limit photosynthesis (Morison et al, 2005) but depend on species and leaf anatomy (Lawson and Morison, 2006).…”
Section: Stomatal Patterningsupporting
confidence: 81%
“…Measurements of maximum and actual photosynthetic efficiency were identical to the wild type in areas with stomata; however, leaf areas without stomata showed lower maximum and actual photosynthetic efficiency, illustrating that stomatal patterning determined CO 2 concentration and photosynthesis across the leaf lamina and that lateral fluxes of gas could not compensate for reduced vertical diffusion as a result of reduced stomatal numbers (Büssis et al, 2006). This work agrees with reports that suggest that lateral fluxes can limit photosynthesis (Morison et al, 2005) but depend on species and leaf anatomy (Lawson and Morison, 2006).…”
Section: Stomatal Patterningsupporting
confidence: 81%
“…However, it may be that bundle sheath cells cannot increase rates of CO 2 assimilation to dissipate EEE (Fryer et al, 2003). This notion comes from observations that CO 2 for photosynthesis in bundle sheath cells may be produced from malate transported from the roots (Hibberd and Quick, 2002) and not from the atmospheric CO 2 , which is unlikely to exhibit significant rates of diffusion from stomatal cavities to vascular tissues in photosynthesizing leaves (Morison et al, 2005). The combination of high rates of electron transport combined with a limited capacity for CO 2 fixation would favor the photoreduction of O 2 and increased production of H 2 O 2 by the water-water cycle (Fryer et al, 2003).…”
Section: Tissue-specific and Subcellular Sources Of Ros For Signalingmentioning
confidence: 99%
“…Evidence supportive of this was presented by Hassiotou et al (2009a), who showed that in the genus Banksia, encryption increases with increasing leaf lamina thickness. Whether or not the diffusion resistance within the intercellular air spaces affects photosynthesis is dependent on the leaf anatomy and porosity, the cell shape and packing, and the pattern of stomatal openings (Morison et al, 2005). Facilitated diffusion by crypts may be particularly beneficial for thick leaves with densely packed mesophyll cells.…”
mentioning
confidence: 99%